Analisis keefektifan pembelajaran berbasis kurikulum 2013 di Sekolah Dasar - Kasmawati Kasmawati (Universitas Negeri Makassar, 2017)
This research aim to know image of domination of teacher to innovation of study bases on curriculum 2013, level of education of teacher, study effectiveness bases on curriculum 2013, and bearing between dominations to innovation of study and level of education of teacher with study effectiveness bases on curriculum 2013 in Town Elementary School Makassar. This research applies quantitative approach with research type of deskriptif-korelasional is having the character of one way. Research variable that is: domination of teacher to innovation of study bases on curriculum 2013 (X1) and level of education of teacher (X2) as independent variable, and execution effectiveness of study of curriculum 2013 as dependent variables. Population of Research that is all schoolteacher Dasar Kota Makassar teaching matter based on curriculum 2013 counted 17, then pulled sample in cluster sampling counted 3 district with category closest, medium, and far counted 6 school with teacher 56 as responder. Data collecting applies enquette and documentation, while data processing applies descriptive statistical analysis and statistical analysis inferensial applies correlation product moment, multiple correlation, and test t. Result of research that is: (1) level of domination of teacher to innovation of study bases on curriculum 2013 in Town Elementary School Makassar pertained masters, (2) level of education of teacher in Town Elementary School Makassar most of graduate Strata Satu ( S-1), (3) study effectiveness bases on curriculum 2013 in Town Elementary School Makassar pertained effective, and (4) there is positive correlation signifikan either parsially and also together between dominations of teacher to innovation of study bases on curriculum 2013 and level of education of teacher with study effectiveness bases on curriculum 2013 in elementary school Kota Makassar. Mean, increasingly good level of domination of teacher to innovation of study bases on kurukulum 2013 and supported by level of education of teacher, hence increasingly effective also study process bases on curriculum 2013.